Boolean Algebra

From TRCCompSci - AQA Computer Science
Jump to: navigation, search

Boolean Algebra Precedence

the order of precedence for boolean algebra is:

  1. Brackets
  2. Not
  3. And
  4. Or

Boolean Identities

TRC Video

https://www.youtube.com/watch?v=ym73-rgnrOQ

Using AND

A.1=A

This equation means that the output is determined by the value of A. So if A =0, The output is 0, and vice versa.

0.A=0

Because there is a 0 in this equation, the output of this will always be 0 regardless of the value of A.

A.A=A

The output is determined by A alone in this equation. This can be simplified to just "A".

A.¯A=0

Here the output will be 0, regardless of A's value. A would have to be 1 and 0 for the output to be 1. This means we can simplify this to just 0.

Using OR

0+A=A

0 or A can be simplified as just A.

1+A=1

1 or A can be simplified as just 1.

A+A=A

A or A can be simplified as just A.

¯A+A=1

NOT A or A can be simplified as just 1.

Boolean Laws

TRC Video

https://www.youtube.com/watch?v=Cdqj4XDsUVY

Commutative Law

The Commutative Law is where equations are the same no matter what way around the letters are written. For example

A+B=B+A

or

A.B=B.A

Associate Law

If all of the symbols are the same it doesn't matter which order the equation is evaluated.

A+(B+C)=B+(A+C)

A+(B+C)=B+(A+C)

A+(B+C)=C+(A+B)

So:

A.(B.C)=B.(A.C)

A.(B.C)=B.(A.C)

A.(B.C)=C.(A.B)

Distributive Law

The distributive law is these two equations.

A.(B+C)=A.B+A.C

A+(B.C)=(A+B).(A+C)

This is essentially factorising or expanding the brackets, but you can also remove the common factor:

A.B+A.C=A.(B+C)

A+B.A+C=A+(B.C)

You can also remove the common factor if you only have 1 term on one side:

A.(A+B)=(0+A).(A+B)

A+(A.B)=(1.A)+(A.B)

if the symbol inside the brackets is a '+' you can add '+0' or if the symbol inside the brackets is '.' you can add '.1'. Doing this will not change the nature of the brackets because 'A' is the same as 'A+0' and is the same as 'A.1'.

Redundancy Law

Law 1 :

A+(¯A.B)=A+B

Proof :

=A+(¯A.B)=A+B=(A+¯A)(A+B)=1.(A+B)=A+B


Law 2:

A.(¯A+B)=A.B

Proof :

=A.(¯A+B)=A.¯A+A.B=0+A.B=A.B


Law 3:

A.(A+B)=A

Proof using distributive law:

A.(A+B)=(0+A).(A+B)

So: A+(0.B)

So: A+0=A


Law 4:

A+(A.B)=A

Proof using distributive law:

A+(A.B)=(1.A)+(A.B)

So: A.(1+B)

So: A.1=A

Identity Law

This is also in the identities section:

A.A=A

A+A=A

Negation Law

Just like in any other logic negating a negative is a positive so:

¯¯A=A

Solving Boolean Equations

Solving equations is a matter of applying the laws of boolean algrebra, followed by any of the identities you can find:

TRC Video

https://www.youtube.com/watch?v=N1r1D__NMGg

Example 1

𝐶+(𝐶.𝐷)


Take out the common factor C:

(C.D)+(C.1)=C.(D+1),

We know that 1+A=1,

Therefore, C.1,

Use identity A.1=A,

Answer = C


Example 2

A.(C+A)



|Use Distributive Law|

->(A.C)+(A.A)

|Use Identity| A.A=A

->(A.C)+A

|This is the same as writing (could straight apply redundancy rule here)|

->(A.C)+(A.1)

|Take out the common factor|

->A.(C+1)

|Use Identity| C+1 = 1

->A

Example 3

𝐵.(𝐴+¯𝐵)


B.(A+ NOT B) REDUNDANCY (A + NOT B) REDUNDANCY

ANSWER = NOT B

Example 4

𝑋.(¯𝑋+𝑌)


𝑋.¯𝑋=0

0+𝑌=𝑌

Example 5

𝑋.(X+¯Y)


(0+𝑋).(X+¯Y)

𝑋+(0.¯Y)

𝑋+(0)

𝑋

Example 8

𝐷.𝐸+𝐸.¯𝐷


D.E+E.D Distributivetive Law D.(E+D) Redundancy Law D

Example 13

(¯A+¯B).B


Expand the brackets: (¯A.B)+(¯B.B)

Not B AND B = 0: ¯A.B)+(0)

Something OR 0 is Something: ¯A.B

Example 14

¯B+(A.B)


(B) + (A.B) Distributive Law. (B + A) . (B + B) Not B cancels out. B + A . 1 = B+A


Example 19

(X+Y).(X+¯Y)



Distributive:
X.(Y+¯Y)
Identity laws:
Y+¯Y=1

X.1=X

Alternative

X.X+X.¯Y+Y.X+Y.¯Y Expanding the brackets

X+X.¯Y+Y.X+0 Use of X.X=X and Y.¯Y=0

X+X(¯Y+Y) Taking X out of the brackets

X+X(1) Use of Y+¯Y=1

X(1)

X

End of Page